Problematika Hukum Prapenuntutan dalam Pengembalian Berkas Acara Pemeriksaan oleh Penuntut Umum kepada Penyidik - Andin Wisnu Sudibyo; Ade Saptomo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the legal vacuum that occurs in the pre-prosecution process, especially related to the absence of time limits and frequency of return of examination report files (BAP) between investigators and public prosecutors. This vacuum has the potential to hinder the principle of fast, simple, and low-cost justice that should be applied in the Indonesian criminal justice system. This study proposes solutions in the form of setting clear time limits, improving coordination between investigators and public prosecutors, and providing training to improve human resource capacity. In addition, the application of sanctions for parties who violate the provisions of pre-prosecution is an important step to ensure the smooth running of the judicial process. This study is expected to contribute to increasing the efficiency of the criminal justice system in Indonesia.